Comparison of 90-Day Mortality After Open Pancreaticoduodenectomy in Low-Volume VS High-Volume groups: A Retrospective Analysis - Saleh Abujamra,; Ferial Khomaise,; Bart Smet,; Yousif Hassan,; Afaf Abushaala,; Mohammed Bin Khalil,; Kefah Ibrahim,; Yasmine Hajjaji,; Salah Eddine Jomaa,; Murad Abeed,; Ahmed Alkmeshi, (AlQalam Journal of Medical and Applied Sciences, 2026)
Hospital volume is an important factor in outcomes of complex surgeries like pancreaticoduodenectomy. High-volume centers generally report lower mortality due to surgical experience, multidisciplinary teams, and structured postoperative care [1,2]. To compare 90-day postoperative mortality after open pancreaticoduodenectomy between a low-volume group in Libya (AlSaqya clinic) and a high-volume Belgian group (Hospital S7, data from RIZIV/INAMI Convention, Belgian Cancer Registry Team).” A retrospective review was performed for patients undergoing open pancreaticoduodenectomy between 2019 and 2023. Low-volume group data included 21 patients from Alsaqya Hospital, Libya, while the high-volume Belgian group included 2,572 patients. Only open surgery cases were included for mortality comparisons. Patient characteristics, including age, sex, ASA, ECOG, Charlson Comorbidity Index, tumor type (malignant and neuroendocrine), and surgical approach, were recorded. Mortality was analyzed using Relative Risk (RR), 95% Confidence Intervals (CI), and Fisher’s Exact Test. The 90-day mortality rate was 9.5% for the low-volume group and 5.0% in the high-volume group (RR = 1.89, 95% CI: 0.46–7.76; p = 0.36). Patients in the low-volume group had higher comorbidities (mean Charlson Index 4.71 vs. 1.33) and predominantly malignant tumors (20/21), while the high-volume group included both malignant and neuroendocrine tumors. All patients in both groups underwent open surgery. Age, sex distribution, ASA classification, and ECOG performance status were similar between the two groups. Mortality was higher in the low-volume group, but the difference was not statistically significant. These findings highlight the importance of hospital experience, multidisciplinary care, and structured perioperative management. Establishing specialized centers and centralizing complex pancreatic surgery, alongside collaboration with high-volume groups and optimization of local protocols, may further improve outcomes in low-volume settings.